Das Melanom - Schiller, Martin; Hassel, Jessica C. (Der Radiologe, 2015)
Clinical issueThe incidence of melanoma has rapidly increased in the last decades. Most relevant for patient prognosis is the tumor thickness, hence an early diagnosis is crucial.Standard treatmentThe basis of treatment is at the primary tumor stage and excision of regional metastases with curative intention.Treatment innovationsTargeted therapies, such as BRAF and MEK inhibitors have the advantage of a rapid response even in highly advanced stages of the disease.Diagnostic work-upFor routine diagnostics ultrasound, computed tomography (CT), fluorodeoxyglucose positron emission tomography CT (FDG-PET/CT) and magnetic resonance imaging (MRI) are used.Performance and achievementsIn the treatment of distant metastases new treatment options are available which more than doubled patient survival rates. Especially immune therapies with immune checkpoint blockers, such as ipilimumab or PD-1 antibodies can lead to long-term survival of patients. In contrast to chemotherapy these new substances have characteristics which make new demands on radiologists related to the possibility of pseudoprogression in immune therapies, which make it necessary to use other response criteria. In addition, autoimmune phenomena, such as a sarcoid-like reactions may mimic new metastases and should be included in the differential diagnosis. BRAF inhibitors may lead to cystic conversions of metastases which again require an evaluation beyond the response evaluation criteria in solid tumors (RECIST), e.g. with the adapted Choi criteria.Practical recommendationsClose interdisciplinary communication, functional imaging methods and adapted response criteria, such as the immune-related response criteria will optimize radiological evaluations of melanoma.